Age differences in perceptions of gerotranscendence: An examination of cosmic dimension behaviors. Issue 3 (2nd July 2016) - Buchanan, Jeffrey A.; Ebel, Donald; Garcia, Sandra; VandeNest, Felicia J.; Omlie, Christina C.
ABSTRACT: The theory of gerotranscendence contends that as we age, a shift in meta-perspective from a materialistic and pragmatic view of the world to a cosmic and transcendent one occurs. The cosmic dimension of gerotranscendence is a central component of the theory and is manifested in various ways. The purpose of this study was to examine age differences in perceptions of cosmic gerotranscendence. Results indicated that older adults rated cosmic gerotranscendent behaviors as less concerning and unusual compared to younger adults even when controlling for familiarity with these behaviors. Implications in terms of cross-generational interactions are discussed.